2019
DOI: 10.1508/cytologia.84.247
|View full text |Cite
|
Sign up to set email alerts
|

New Chromosome Numbers in <i>Scorzonera</i>, subgenera <i>Podospermum</i> and <i>Pseuodopodospermum</i> (Cichorieae, Asteraceae)

Abstract: Somatic chromosome numbers of seven Scorzonera L. species collected from different localities in Iran were counted. Except for S. mucida with 2n=28, the other species exhibited a somatic number of 2n=14. The chromosome numbers support the basic number (x=7) of Scorzonera. The chromosome numbers in S. tunicata, S. kandavanica, S. persepolitana, S. mucida, and S. raddeana are reported for the first time. Chromosome numbers in S. luristanica and S. songorica are different from those of the previous reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…2016;Norouzi & al. 2016;Hatami & al. 2019), which included additional species that were not considered members of S. subg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2016;Norouzi & al. 2016;Hatami & al. 2019), which included additional species that were not considered members of S. subg.…”
Section: Discussionmentioning
confidence: 99%
“…We consider them as separate species based on differences in achene and phyllary characters (see Notes under S. mucida). Hatami & al. (2019) recently found that chromosome number and ploidy are also different between these species: tetraploid and 2n = 28 in S. mucida in contrast to diploid and 2n = 14 in S. tunicata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation